FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT KABUPATEN BATUBARA MENJADI NASABAH BANK SYARIAH INDONESIA - Nurmila Rizky; M. Yarham; Ridwana Siregar (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine whether promotion, knowledge and location influence people's interest in saving at Bank Syariah Indonesia KCP Batubara. This type of research is descriptive quantitative by obtaining primary data from questionnaires that are given to respondents. The method of determining the sample by taking as many as 100 respondents using the slovin formula. The data obtained is then processed with the SPSS program. The results obtained for the knowledge variable tcount 3.975, promotion variable tcount 4.701, location variable tcount 3.119 and ttable 0.1654 (tcount > ttable) and significant 0.001 <0.05. The results of the t-test showed that the promotion and location variables had a significant effect, while the knowledge variable did not have a significant effect. This research is expected to be a source of reference and reference for the Batubara community in saving at BSI